Comparison of conventional pap smear with liquid based cytology, and assessment of the effectiveness and feasibility of liquid-based cytology over conventional pap smear in rural tertiary care centre - Sharma, Sheela; Singh, Neetu; Sinha, Amrita; Jain, Smriti (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Cervical cancer is the second most common cancer in women in India. So, detection of its premalignant lesions is of utmost importance, which can be easily done by screening methods. Screening programmes for cervical cancer using the conventional pap smear (CPS) technique have been in place since decades. However, CPS technique has many limitations. To overcome these limitations liquid-based cytology (LBC) was introduced in the mid 1990 as a better tool for processing cervical samples. The aim of present study is to compare CPS with LBC and to assess the diagnostic accuracy and cost effectiveness of LBC in rural tertiary care centre. Methods: The study was conducted over a period of 2 years at Rama medical college, Mandhana, Kanpur. All women presenting to gynaecological OPD with symptoms and signs suspicious of cervical malignancy were selected for paired samples of conventional pap and LBC. Colposcopy and biopsy were sought which correlated with cytologic findings. Results: A maximum number of cases were in the reproductive age group, most common age of presentation being 40-49 years (27.3%) followed by 30-39 years (25.3%). A majority of patients were presented with a complaint of discharge per vagina 176 (58.7%), followed by pelvic pain 154 (51.3%). Only 4 patients were found to have unsatisfactory smear in LBC (1.33%) while 22 patients had unsatisfactory smear in conventional PAP (7.33%). LBC showed presence of endocervical cells in almost all patients 290 (97.97%). Candida bodies were not evident in LBC smears while the CPS showed presence candida bodies in 4 cases. Conclusions: Both the screening methods are very effective and sensitive in the detection of premalignant lesions with slight discordance of grade on histology. Thus, we conclude that cervical cytology is very effective in the detection of premalignant lesions with the sensitivity of almost 100%. In developing countries such as India, where finances pose a major problem, conventional method is as good as LBC.